The great game : the struggle for empire in central Asia - Hopkirk, Peter (New York : Kodansha International, 1992)
The Great Game, a deadly struggle in the last century between secret agents of the two superpowers--Victorian Britain and Tsarist Russia--has once again become ominously topical, as a new power struggle begins in Central Asia.
The Beginnings. 1. The Yellow Peril. 2. Napoleonic Nightmare. 3. Rehearsal for the Great Game. 4. The Russian Bogy. 5. All Roads Lead to India. 6. The First of the Russian Players. 7. A Strange Tale of Two Dogs. 8. Death on the Oxus. 9. The Barometer Falls -- The Middle Years. 10. 'The Great Game'. 11. Enter 'Bokhara' Burnes. 12. The Greatest Fortress in the World. 13. The Mysterious Vitkevich. 14. Hero of Herat. 15. The Kingmakers. 16. The Race for Khiva. 17. The Freeing of the Slaves. 18. Night of the Long Knives. 19. Catastrophe. 20. Massacre in the Passes. 21. The Last Hours of Conolly and Stoddart. 22. Half-time -- The Climactic Years. 23. The Great Russian Advance Begins. 24. Lion of Tashkent. 25. Spies Along the Silk Road. 26. The Feel of Cold Steel Across His Throat. 27. 'A Physician from the North'. 28. Captain Burnaby's Ride to Khiva. 29. Bloodbath at the Bala Hissar. 30. The Last Stand of the Turcomans. 31. To the Brink of War. 32. The Railway Race to the East. 33. Where Three Empires Meet. 34. Flashpoint in the High Pamirs. 35. The Race for Chitral. 36. The Beginning of the End. 37. End-game.
Includes bibliographical references (p. 527-542) and index.
Keywords: Eastern question (Central Asia); Afghan Wars; Asia, Central -- Politics and government; Asia, Central -- Relations -- Soviet Union; Soviet Union -- Relations -- Asia, Central; Asia, Central -- Relations -- Great Britain; Great Britain -- Relations -- Asia, Central